2006
DOI: 10.1016/j.cplett.2005.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplatelets made from MoS2 and WS2

Abstract: Free clusters of the layered semiconductor materials of type MS 2 (M = Mo, W) are studied using mass and photoelectron spectroscopy and compared to theoretical predictions. In contrast to carbon fullerenes, these clusters prefer planar platelet structures. The dangling bonds at the edges are stabilized by excess S atoms. For W n S À m we find that platelet structures dominate for clusters larger than W 10 S 30 , the most stable species are W 15 S 42 and W 21 S 56. These platelets have a metallic character and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
6
53
0
Order By: Relevance
“…Therefore, the exact reaction mechanism that leads to the formation of the nanooctahedra remains still an open issue. Recently several papers were published concerning triangular monolayers of MoS 2 and WS 2, which presented both experimental and theoretical grounds for the relative stability of such structures (25)(26)(27)(28). Apparently, these structures are stabilized by the addition of excess S atoms in the form of S 2 pairs at the edges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the exact reaction mechanism that leads to the formation of the nanooctahedra remains still an open issue. Recently several papers were published concerning triangular monolayers of MoS 2 and WS 2, which presented both experimental and theoretical grounds for the relative stability of such structures (25)(26)(27)(28). Apparently, these structures are stabilized by the addition of excess S atoms in the form of S 2 pairs at the edges.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, pentagonal projections and triangular projections of MoS 2 were also detected in the soot, possibly representing a pentagonal bi-pyramid and a triangular prism, respectively, or a distorted version of them also constructed by triangular faces. Moreover, experiments and DFT calculations indicated that the WS 2 (MoS 2 ) triangular monolayers were metallic-like as a result of the sulfur pairs at the structure rims (25). The absence of the triangular faces in the soot produced by the laser ablation experiments may be attributed to the difficulty in detecting these minute monolayers even with advanced microscopes.…”
Section: Resultsmentioning
confidence: 99%
“…James et al [19] reported MoOC, Mo O O OS, and MoON cluster formation O in the gas phase. Mo and W disulfide nanoplatelets in the gas phase have been studied by Bertram et al [20]. Gemming et al [21] explored the small metal sulfide M x S y (M ϭ Mo, W; x ϭ 1, 2, 4; y ϭ 1-12) clusters using theoretical calculations and mass spectrometry.…”
mentioning
confidence: 99%
“…In the gas phase, the most stable platelet is W 15 S 42 and the smallest observed platelet is W 10 S 30 . [23][24][25] The octahedral shape of the nested inorganic fullerenes indicates that two-dimensional triangular structures are preferred by MoS 2 and WS 2 . No "single-wall" real fullerenes have been found until today.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that the particles in the first maximum are one-dimensional chains and two-dimensional platelets. [23][24][25] Here, we focus on the structure determination of the larger clusters in the second maximum. These clusters are studied with anion photoelectron spectroscopy, scanning transmission electron microscopy, and scanning tunneling microscopy.…”
Section: Introductionmentioning
confidence: 99%